Estimating the Effective Interest Rate. - Thomas, Arthur L. (The Accounting Review, 1968)
Abstract At some point in their education, business students deal with a "Time Value of Money" and with interest rates. The effective interest rate on any form of debt is that discount rate at which the present value of the payments made by the borrower equals the amount actually borrowed. So, it is helpful to have a way of estimating the effective rate without using present value tables. The efforts of lenders to justify their finance charges have led to great variety and inconsistency in the language used for discussing installment contracts. The contract's "principal" is the difference between the cash price and any down payment. The contract's "finance charge" is the difference between the cash price and the total amount paid by the credit purchaser. Often, the economic and legal definitions of "interest" are much narrower than what is included in this notion of the "finance charge." Lenders often regard this finance charge as including costs of credit investigation, insurance, account service fees and the like-in addition to the "pure" interest charge.